Influence of factors on mammographic density in premenopausal Chinese women. Issue 4 (July 2016) - Yang, Yaping; Liu, Jieqiong; Gu, Ran; Hu, Yue; Liu, Fengtao; Yun, Miaomiao; Xiao, Qiaozhen; Wu, Mei; Liu, Qiang; Su, Fengxi
Abstract : Mammographic density is an independent strong risk factor for breast cancer. However, the influence of factors on mammographic density in premenopausal women remains unclear. In the Southern Professional Women Breast Cancer Screening Project, we assessed the associations between mammographic density and its influential factors using multivariate logistic regression in premenopausal women adjusting for BMI, age, duration of breastfeeding, number of live births, and breast size. A total of 1699 premenopausal women aged 27 to 57 years, who had been screened by mammography, were enrolled in this cross-sectional study. Overall, 85.2% were categorized as having dense breasts (BI-RADS density 3 and 4) and 14.8% as having fatty breasts (BI-RADS density 1 and 2). In multivariate and logistic regression analysis, only BMI and age were significantly negatively correlated with mammographic density in premenopausal women ( P <0.001). No significant associations between mammographic density and number of deliveries, breastfeeding duration, education level, family history of breast cancer, as well as breast size and sleep quality, were identified in the study. Age and BMI are negatively associated with mammographic density in premenopausal Chinese women. Information on the influential factors of mammographic density in premenopausal women might provide meaningful insights into breast cancer prevention.